Biomarkers of cervicovaginal fluid for the diagnosis of cervical diseases associated with human papilloma virus (literature review) - Vera N. Prilepskaya; Anna N. Mheryan; Aida S. Akopian; Niso M. Nazarova; Elmira R. Dovletkhanova; Patimat R. Abakarova; Natalia L. Starodubtseva (IP Berlin A.V., 2020)
Human papillomavirus (HPV) is one of the main pathogens of genital tract infections, which can lead to malignant transformation of cells of the cervix, vagina, vulva and anus. Approximately 90% of cervical intraepithelial neoplasia cases and 99% of cervical cancer cases occur in HPV-positive patients. However, the presence of HPV in the patients body can not be considered as a marker of progression or regression of the pathological process. The need to determine further tactics of examination and management of women with HPV-associated diseases of the cervix States the search for molecular genetic markers of neoplastic transformation in order to predict the risk of cervical neoplasia and cervical cancer. Diagnostic systems based on determination of biomarkers in cervicovaginal fluid (CVJ) can become convenient for application in clinical practice. The panel of CVJ proteins allows to make the exact characteristic of a condition of bodies of female reproductive system, including at neoplastic processes of a cervix of a uterus. The biomarkers identified in the CVJ can be used as informative tests to improve the accuracy of diagnosis of pathological changes in the cervix and to determine the risk criteria for the development of malignancy.